P072: Exploring definitions of "unnecessary care" in emergency medicine: a qualitative analysis of physician survey responses. (15th May 2017) - Krebs, L.; Gaudet, L.; Chartier, L.B.; Holroyd, B.R.; Dowling, S.; Cheng, A.H.; Villa-Roel, C.; Campbell, S.G.; Couperthwaite, S.; Rowe, B.H.
Abstract : Introduction: Recently, campaigns placing considerable emphasis on improving emergency department (ED) care by reducing unnecessary tests, treatments, and/or procedures have been initiated. This study explored how Canadian emergency physicians (EPs) conceptualize unnecessary care in the ED.Methods: An online 60-question survey was distributed to EP-members of the Canadian Association of Emergency Physicians (CAEP) with valid emails. The survey explored respondents awareness/support for initiatives to improve ED care (i.e., reduce unnecessary tests, treatments and/or procedures) and asked respondents to define "unnecessary care" in the ED. Thematic qualitative analysis was performed on these responses to identify key themes and sub-themes and explore variation among EPs definitions of unnecessary care.Results: A total of 324 surveys were completed (response rate: 18%); 300 provided free-text definitions of unnecessary care. Most commonly, unnecessary ED care was defined as: 1) performing tests, treatments, procedures, and/or consults that were not indicated or potentially harmful ( n =169) and/or 2) care that should have been provided within a non-emergent context for a non-urgent patient ( n =143). Emergency physicians highlighted the role of system-level factors and system failures that result in ED presentations as definitions of unnecessary care ( n =69). They also noted a distinction between providing necessary care for a non-urgent patient and performing inappropriate/non-evidenced based care. Finally, a tension emerged in their description of frustration with patient expectations ( n =17) and/or non-ED referrals ( n =24) for specific tests, treatments, and/or procedures. These frustrations were juxtaposed by participants who asserted that "in a patient-centred care environment, no care is unnecessary" (Participant 50; n =12).Conclusion: Variation in the definition of unnecessary ED care is evident among EPs and illustrates that EPs' conceptualization of unnecessary care is more nuanced than current campaigns addressing ED care improvements represent. This may contribute to a perceived lack of uptake or support for these initiatives. Further exploring EPs perceptions of these campaigns has the potential to improve EP engagement and influence the language utilized by these programs.